Photography Workshop for School Dropout Youth in Nagari Batu Bulek, North Lintau Buo District, Tanah Datar Regency - Yenni Darvina Yulidar (Pelita Eksakta, 2022)
Tourism in the era of the COVID-19 pandemic could be suspended if entrepreneurs, institutions, ormanagers do not immediately switch to using digital technology. Promotion of tourism, offers,destinations, hotels, culinary, souvenirs, and everything related to tourism requires digital technology.Through this technology, photos or videos related to tourism promotion can be presented. Photos orvideos that are made professionally and presented briefly, concisely, and precisely, are the mainattraction for tourists. Therefore, the presence of a professional photographer is needed. Puncak Pato isthe second most favored destination in Tanah Datar Regency, after the Pagaruyung Traditional House.This tourist location is located in Nagari Batu Bulek, North Lintau Buo District, Tanah Datar Regency,West Sumatra. In this village there is a group of out of school youth. They don't have permanent jobs.This youth group has a strong interest in photography, but does not yet have sufficient competence.Through the Community Partnership Program, the Community Service Group of the Faculty ofMathematics and Natural Sciences UNP provides workshops to improve their competence inphotography. The results of the pre-test and post-test for the knowledge and skills of the participants,which consisted of 7 people, showed that there had been an increase in the competence of theparticipants. It is hoped that they can become professional photographers who are the spearhead of thepromotion of Puncak Pato and other tours in Tanah Datar Regency throughout the world.